2023
DOI: 10.1371/journal.pbio.3002028
|View full text |Cite|
|
Sign up to set email alerts
|

TDP-43 and other hnRNPs regulate cryptic exon inclusion of a key ALS/FTD risk gene, UNC13A

Abstract: A major function of TAR DNA-binding protein-43 (TDP-43) is to repress the inclusion of cryptic exons during RNA splicing. One of these cryptic exons is in UNC13A, a genetic risk factor for amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). The accumulation of cryptic UNC13A in disease is heightened by the presence of a risk haplotype located within the cryptic exon itself. Here, we revealed that TDP-43 extreme N-terminus is important to repress UNC13A cryptic exon inclusion. Further, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…This suggests the merit of ASO targeting STMN2 cryptic splicing for clinical application. TDP-43 also acts as a main repressor of the inclusion of UNC13A cryptic exons, which is a genetic risk factor for ALS and frontotemporal dementia (FTD) (Brown et al, 2022;Koike et al, 2023;Ma et al, 2022;Mehta et al, 2023). How the inclusion of UNC13A cryptic exons is involved in the pathogenesis of these ALS/FTD remains to be elucidated.…”
Section: Cryptic Rna Splicings Of the Targets Of Tdp-43mentioning
confidence: 99%
“…This suggests the merit of ASO targeting STMN2 cryptic splicing for clinical application. TDP-43 also acts as a main repressor of the inclusion of UNC13A cryptic exons, which is a genetic risk factor for ALS and frontotemporal dementia (FTD) (Brown et al, 2022;Koike et al, 2023;Ma et al, 2022;Mehta et al, 2023). How the inclusion of UNC13A cryptic exons is involved in the pathogenesis of these ALS/FTD remains to be elucidated.…”
Section: Cryptic Rna Splicings Of the Targets Of Tdp-43mentioning
confidence: 99%
“…Loss of TDP-43 function has been linked to neurodegeneration via disruptions in the splicing repression of nonconserved cryptic exons (7,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Indeed, compelling evidence from recent studies suggests that cryptic exons found in the genes STMN2 (16)(17)(18) and UNC13A (21,22) may contribute significantly to disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging high depth 3'-end sequencing, we found a widespread switch towards distal polyadenylation (PA) site usage across ALS subtypes relative to controls. To explore this differential alternative PA (APA), we developed APA-Net, a deep neural network model that uses transcript sequence and expression levels of RNA-binding proteins (RBPs) to predict cell-type specific APA usage and RBP interactions likely to regulate APA across disease subtypes.The molecular underpinnings of cortical dysfunction associated with FTLD in ALS remain unclear but has been linked with changes in expression and/or subcellular localizations of various RNA binding proteins (RBPs), including TDP-43 7-10 , the most prevalent disease pathology in ALS/FTLD, as well as FUS 11 , SFPQ 12,13 , TIA1 14 , and heterogeneous ribonucleoproteins (HNRNPs) 15,16 . RBPs regulate diverse functions across cell types, including chromatin dynamics 10,[17][18][19] , transcription 7-10 , auto-regulation 20,21 , alternative splicing (AS) 8 , and alternative polyadenylation (APA) 20,[22][23][24][25] .…”
mentioning
confidence: 99%
“…The molecular underpinnings of cortical dysfunction associated with FTLD in ALS remain unclear but has been linked with changes in expression and/or subcellular localizations of various RNA binding proteins (RBPs), including TDP-43 7-10 , the most prevalent disease pathology in ALS/FTLD, as well as FUS 11 , SFPQ 12,13 , TIA1 14 , and heterogeneous ribonucleoproteins (HNRNPs) 15,16 . RBPs regulate diverse functions across cell types, including chromatin dynamics 10,[17][18][19] , transcription 7-10 , auto-regulation 20,21 , alternative splicing (AS) 8 , and alternative polyadenylation (APA) 20,[22][23][24][25] .…”
mentioning
confidence: 99%